2015
DOI: 10.1111/2047-3095.12091
|View full text |Cite
|
Sign up to set email alerts
|

The Nursing Diagnosis Disturbed Thought Processes in Psychiatric Patients: Prevalence and Associated Characteristics

Abstract: Patients with DTP may require a more complex nursing attention as its presence is associated with specific care needs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Both diagnoses describe aspects related to symptoms of mental health disorders. Confirming this statement, Escalada‐Hernandez and Marin‐Fernandez () demonstrated an association between the presence of “ Disturbed Thought Process ” and the severity of mental disorders. Although these diagnoses were excluded from the NANDA‐I classification, further research is essential for a better understanding of these concepts and their relevance for psychiatric nursing care.…”
Section: Discussionmentioning
confidence: 76%
“…Both diagnoses describe aspects related to symptoms of mental health disorders. Confirming this statement, Escalada‐Hernandez and Marin‐Fernandez () demonstrated an association between the presence of “ Disturbed Thought Process ” and the severity of mental disorders. Although these diagnoses were excluded from the NANDA‐I classification, further research is essential for a better understanding of these concepts and their relevance for psychiatric nursing care.…”
Section: Discussionmentioning
confidence: 76%
“…The category specific patient population: psychiatric patients includes six studies developed in psychiatric inpatient care facilities (Abderhalden et al., ; Escalada‐Hernández & Marín‐Fernández, ; Sales Orts, ; Stefan et al., ; Ugalde Apalategui & Lluch Canut, ) and two in community psychiatric care services (Boomsma, Dingemans, & Dassen, ; Lluch Canut et al., ). Additionally, another study on symptom monitoring after alcohol dependence show data about the frequency of DTPs (Murphy, ).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, both of them suggested that the frequency of DTPs was higher than 30% in patients with medical diagnoses such as schizophrenia, disorders of adult personality and behaviors, substance use disorders, depression, or bipolar disorders. On the other hand, one of these studies found a statistically significant relationship between the presence of DTPs, and both found a higher degree of severity of problems associated with mental illness and a higher number of nursing diagnoses recorded in the care plan (Escalada‐Hernández & Marín‐Fernández, ).…”
Section: Resultsmentioning
confidence: 99%
“…These data indicate the urgent need for actions to protect the lives of these people in psychological distress, and the insertion in the NC modality is a strategy of the psychosocial model of care and protection. However, the myth of dangerousness still appears rooted in common sense, allowing the fear of users of mental health services, causing the treatment of these people to continue in the form of segregation in hospitalizations in a psychiatric hospital environment (26)(27) .…”
Section: Discussionmentioning
confidence: 99%